On and of paper - Miller, Gail I., author; Dormer, James T., advisor; Orman, Jack L., committee member; Crocker, David A., committee member (Colorado State University. Libraries, 1984)
A personal interest and belief in nature has been the basis for the creation of this series of reflective, interior landscapes. Color is used to express subtle atmospheric light, and space appears to extend beyond the picture plane, which is defined by an abstract, geometric structure. These landscapes reach for the universal essence of nature rather than a sense of place and present a moment of timelessness within the ever changing.
Keywords: Paper, Handmade; Lithography; Intaglio printing; Collage; Landscapes